2022
DOI: 10.1021/jacs.2c09823
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solvent on Selective Catalytic Reduction of Nitrogen Oxides with Ammonia over Cu-CHA Zeolite

Abstract: The copper-exchanged zeolite Cu-CHA has received considerable attention in recent years, owing to its application in the selective catalytic reduction (SCR) of NO x species. Here, we study the NH3-SCR reaction mechanism on Cu-CHA using the hybrid quantum mechanical/molecular mechanical (QM/MM) technique and investigate the effects of solvent on the reactivity of active Cu species. To this end, a comparison is made between water- and ammonia-solvated and bare Cu species. The results show the promoting effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…It was reported that double peaks at 2237 and 2210 cm –1 appeared when N 2 O adsorbed on the catalyst surface or NH 3 oxidation occurred at high temperatures. Therefore, they were denoted as M-NNO species adsorbed on surface cation and further desorbed to gaseous N 2 O. ,,, The peak of 2237 cm –1 was ascribed to the vibration of the NN bond of adsorbed intermediate, possibly NH 2 NO ads , originating from the reaction of adsorbed NO + and NH 3 . , …”
Section: Resultsmentioning
confidence: 99%
“…It was reported that double peaks at 2237 and 2210 cm –1 appeared when N 2 O adsorbed on the catalyst surface or NH 3 oxidation occurred at high temperatures. Therefore, they were denoted as M-NNO species adsorbed on surface cation and further desorbed to gaseous N 2 O. ,,, The peak of 2237 cm –1 was ascribed to the vibration of the NN bond of adsorbed intermediate, possibly NH 2 NO ads , originating from the reaction of adsorbed NO + and NH 3 . , …”
Section: Resultsmentioning
confidence: 99%
“…The first two test cases concern molecules in solution, namely, the amino acid L-histidine in a spherical water droplet, and a more complex haem protein in a water shell solvation model. The third test case is the heterogeneous catalyst chabazite (CHA), a typical zeolitic material with excellent performance in selective catalytic reduction of nitrogen oxides with ammonia [100][101][102], which has recently been studied in our group [103,104]. Finally, hydrogen absorption on an ionic metal oxide ZnO polar surface supporting the hydrogenation of carbon dioxide to methanol is investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Abdul Nasir et al investigated the effect of water and ammonia solvent molecules on the selective catalytic reduction of NO x species by the copper-exchanged zeolite Cu-CHA. 209 The results showed that solvation of the active sites has a strong influence on the energy profile of the catalytic cycle, with differing effects on the oxidative and reductive parts. Liu et al used QM/MM methods to investigate the structure and stability of vanadium-doped active sites in Al-MCM-41, and their potential use as heterogeneous catalysts for the oxidation of furans.…”
Section: Solid State Embeddingmentioning
confidence: 99%